In Vitro Evaluation of the Antifungal Properties of Bixa orellana L. Essential Oil from the Ecuadorian Amazon Against Candida albicans (ATCC 10231) - María Belén Cruz Berrú; María Coraima Mora García; Sandra Luisa Soria Re; Jannys Lizeth Rivera Barreto; Luis Ramón Bravo Sánchez; Matteo Radice; Stefano Manfredini; Reinier Abreu-Naranjo (Life)
Essential oils are investigated due to their biological activity, and the Amazon rainforest, with its rich biodiversity, is a promising source of therapeutic compounds. The aim of this study was to evaluate the essential oil from the leaves of Bixa orellana as an antifungal agent, thus contributing to the search for alternatives that can address the growing resistance to conventional antifungals. B. orellana leaves were collected in the Ecuadorian Amazon and their essential oil was obtained by steam distillation. Their chemical composition was analysed by Gas Chromatography-Mass Spectrometry (GC-MS) and their antifungal activity against Candida albicans was evaluated using the Kirby–Bauer disc diffusion method (ATCC 10231), with nystatin as a positive control. GC-MS analysis revealed the presence of 60 compounds, the main ones being dihydroedulan (27.5%), β-caryophyllene (10.3%), nerolidol (7.21%), trans-β-bergamotene (5.73%), α-santalene (4.94%) and trans-α-bergamotene (4.26%). The essential oil showed moderate antifungal activity against C. albicans, producing an inhibition halo of 13 mm in diameter, which is 48% of the inhibition observed with nystatin (27 mm). The presence of sesquiterpenes, such as β-caryophyllene, known for its membrane-disrupting properties, probably contributes to the observed antifungal effects. The study highlights the potential of B. orellana essential oil as a natural antifungal agent; however, further research is required to evaluate its efficacy against a wider range of pathogenic fungi, its possible synergistic effects with conventional antifungals and its safety and efficacy in vivo.